The public valuation of religion in global health governance: spiritual health and the faith factor - Tine Hanrieder (Contemporary Politics, 2017)
This article explores how the role of religion is evaluated in global health institutions, focusing on policy debates in the World Health Organization (WHO) and the World Bank. Drawing on Luc Boltanski and Laurent Thévenot's pragmatist approach to justification, I suggest that religious values are creative and worldly performances. The public value of religion is established through a two-pronged justification process, combining generalizing arguments with particularizing empirical tests. To substantiate the claim that abstraction alone does not suffice to create religious values in global public health, I compare the futile attempts of the 1980s to add `spiritual health' to the WHO's mandate with the more recent creation of a `faith factor' in public health. While the vague reference to some `Factor X' inhibited the acceptance of spiritual health in the first case, in the second case, `compassion' became a measurable and recognized religious value.
Additional information: Akzeptierte Manuskriptfassung (postprint) / Accepted version (postprint)
Keywords: 330; global health governance; religion; secularism; spiritual health; public justification; valuation theory